Generic protection clauses of legitimate: An antidote for preterition - Pérez Gallardo, Leonardo B. (2021)
Predictability by the testator clauses generic protection of legitimate, which provides the possibility that come upon heirs specially protected after the granting of the will, formulated in terms of general scope entails deemed not preterida daughter is looming testator minor, economically dependent on his father, both at the time of the granting of the will as to the death of that, while it is understood that, although not expressly mentioned, falls in clause generic recognition of legitimarios future, and consequently attributed half of what by legitimate due.